Mathematical simulation of the neutron interaction with matter - Dovbnya, A.N.; Prokhorets, I.M.; Prokhorets, S.I.; Slabospitskiy, R.P.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2004)
The application of neutron beams is important for some fundamental problems in nuclear physics, for fission and fusion reactors, future safety of atomic energy, neutron radioactivation analysis, neutron radiography etc. Solving of such problems is connected with huge material and financial expenses, so the mathematical simulation is widely used. In NSC KIPT GEANT3, GEANT4, our own programs, etc. are used for these purposes. The mathematical models and algorithms of calculation of passage of neutrons with energy up to 14 MeV through homogenous medium with fissionable materials were developed. The simulation of passage of neutrons with energy up to 3 MeV through the plate and cylinder was considered. The obtained results were compared with existing literature data.